A petrochemical study of basaltic layering at Henley Harbour, Labrador, using multidimensional scaling - Greenough, John; Owen, J. (Atlantic Geology, 2003)
ABSTRACT Lack of internal textural evidence for flow tops and small chemical variability among late Proterozoic basalt samples suggest the presence of a single flow at Henley Harbour, Labrador, Canada, despite spectacular, m-scale layering in outcrop. Total chemical variation just slightly exceeds analytical uncertainty for many elements. Multidimensional scaling (MDS) enhances "effective" analytical precision by allowing all data (elements and samples) to be compared simultaneously. Scaling of elements reveals element associations/patterns consistent with igneous controls on distribution, even for alteration-sensitive (Na, K, Sr) elements. MDS also shows that the m-scale layering has a chemical fingerprint. However, to explain chemical variability between layers using mass balance calculations and averaged whole-rock data requires unreasonable (low temperature) phenocryst compositions. Textural features of the m-scale layering record changes in cooling regime between the bottom and center of the flow but chemical variation may reflect changing magma compositions during formation of an inflated flow. However, mass balance calculations suggest that large-scale chemical variation reflects the migration of residual liquid, perhaps as vesicle plumes, within an initially chemically homogeneous flow. Low in the flow (layer 1), metres-long but cm-scale raised and eroded subhorizontal "bands" superficially resemble segregation veins but lack coarse-grained textures. MDS confirms that raised and eroded samples are chemically distinct. Mass balance indicates that banding is not related to phenocryst percentages but may reflect the abundance of a residual liquid resembling the liquid explaining compositional variation between large-scale layers. Alignment of microlites and variations in the quantity of altered residual-liquid glass suggest that banding is related to magma movement during extrusion. It is possible that banding of this type has not been recognized before.